Acceptance of a Nordic, Protein-Reduced Diet for Young Children during Complementary Feeding—A Randomized Controlled Trial - Johansson Ulrica; Lindberg Lene; Öhlund Inger; Hernell Olle; Lönnerdal Bo; Lundén Saara; Sandell Mari; Lind Torbjörn (MDPI, 2022)
Early life is critical for developing healthy eating patterns. This study aimed to investigate the effects of a Nordic, protein-reduced complementary diet (ND) compared to a diet following the current Swedish dietary guidelines on eating patterns and food acceptance. At 4-6 months (mo) of age infants were randomized to a Nordic group (NG, n = 41) or a Conventional group (CG, n = 40), and followed until 18 mo of age. Daily intake of fruits and vegetables (mean +/- sd) at 12 mo was significantly higher in the NG compared to the CG: 341 +/- 108 g/day vs. 220 +/- 76 g/day (p < 0.001), respectively. From 12 to 18 mo, fruit and vegetable intake decreased, but the NG still consumed 32% more compared to the CG: 254 +/- 99 g/day vs. 193 +/- 67 g/day (p = 0.004). To assess food acceptance, both groups were tested with home exposure meals at 12 and 18 mo. No group differences in acceptance were found. We find that a ND with parental education initiates healthy eating patterns during infancy, but that the exposure meal used in the present study was insufficient to detect major differences in food acceptance. This is most likely explained by the preparation of the meal. Nordic produce offers high environmental sustainability and favorable taste composition to establish healthy food preferences during this sensitive period of early life.